Characterisation of nano-thin film GO/TiO2 layers for Kretschmann-based surface plasmon resonance visible sensing using FDTD method - Khairulazdan, N. B.; Mohamed, R.; Berhanuddin, D. D.; Menon, P. S. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
Kretschmann-based surface plasmon resonance (K-SPR) is suitable for biomolecular sensing which provides label-free and quick detection results with real-time analysis. In this work, we have investigated the effect of graphene oxide (GO) with titanium dioxide (TiO2) thin films that are placed in hybrid above metal layers such as gold (Au), silver (Ag) and copper (Cu) with the presence of chromium (Cr) as an adhesive layer. The thickness of the Au, Ag and Cu metal thin films were optimized to 40, 30 and 30 nm, respectively, with a fixed thickness of GO of 2 nm and TiO2 of 1.9 nm. The sensing was evaluated for SPR excitation at three different visible wavelengths of 633, 670 and 785 nm. The performance of sensing was analyzed based on the reflectance intensity and full-width at half-maximum (FWHM) of the spectrum using the finite-difference time-domain (FDTD) method. The sensitivity was calculated for analyte sensing in dielectric mediums of air versus water. The sensitivity increment percentage (%∆S) was determined when comparing analyte detection using Cr/metal and Cr/metal/GO/TiO2 sensor structures. The highest sensitivity of 94.51 deg/RIU was achieved for Cr/Cu/GO/TiO2 K-SPR sensor at 633 nm wavelength.
Optica Applicata, Vol. 51, 2021, nr 4, s. 579-587
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; surface plasmon resonance; FDTD; titanium dioxide; graphene oxide; Kretschmann, biosensor